The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1210/jc.2005-2476
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Hypopituitarism after Traumatic Brain Injury: A Prospective Investigation of Anterior Pituitary Function in the Acute Phase and 12 Months after Trauma

Abstract: GHD is the most common pituitary deficit 12 months after TBI, and 50.9% of the patients had at least one anterior pituitary hormone deficiency. Pituitary function may improve or worsen in a considerable number of patients over 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
265
7
22

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(310 citation statements)
references
References 33 publications
(59 reference statements)
14
265
7
22
Order By: Relevance
“…In these previous studies (5,(7)(8)(9)(10)(11)(12)(13)(14), the percentage of patients with Mod/STBI was higher (56-100%) than that of the patients in our study. In addition to the differences in the study cohorts, the wide range of reported prevalences of hypopituitarism (varying from 15 to 56%) may be attributed to the differences in diagnostic criteria (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Furthermore, some studies included patients in whom, besides a history of TBI, alternative causes of pituitary dysfunction had not been ruled out, such as pre-existent hypopituitarism (6-10, 12, 14), BMI above 30 kg/m 2 (5-10, 12-14), and substance abuse (6-10, 12).…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…In these previous studies (5,(7)(8)(9)(10)(11)(12)(13)(14), the percentage of patients with Mod/STBI was higher (56-100%) than that of the patients in our study. In addition to the differences in the study cohorts, the wide range of reported prevalences of hypopituitarism (varying from 15 to 56%) may be attributed to the differences in diagnostic criteria (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Furthermore, some studies included patients in whom, besides a history of TBI, alternative causes of pituitary dysfunction had not been ruled out, such as pre-existent hypopituitarism (6-10, 12, 14), BMI above 30 kg/m 2 (5-10, 12-14), and substance abuse (6-10, 12).…”
Section: Discussioncontrasting
confidence: 62%
“…In all the 30 patients with Mod/STBI participating in our study, anterior pituitary function was normal. The prevalence of hypopituitarism after TBI that we report is considerably lower than the prevalences reported by recent studies (15-56%) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The aim of our study was to evaluate anterior pituitary function in a patient cohort representative for all the patients with TBI.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations